Studies of 3D directed cell migration enabled by direct laser writing of curved wave topography. (25th February 2019) - Cheng, Daniel; Jayne, Rachael K; Tamborini, Alessio; Eyckmans, Jeroen; White, Alice E; Chen, Christopher S
Abstract: Cell migration, critical to numerous biological processes, can be guided by surface topography. Studying the effects of topography on cell migration is valuable for enhancing our understanding of directional cell migration and for functionally engineering cell behavior. However, fabrication limitations constrain topography studies to geometries that may not adequately mimic physiological environments. Direct Laser Writing (DLW) provides the necessary 3D flexibility and control to create well-defined waveforms with curvature and length scales that are similar to those found in physiological settings, such as the luminal walls of blood vessels that endothelial cells migrate along. We find that endothelial cells migrate fastest along square waves, intermediate along triangular waves, and slowest along sine waves and that directional cell migration on sine waves decreases as sinusoid wavelength increases. Interestingly, inhibition of Rac1 decreases directional migration on sine wave topographies but not on flat surfaces with micropatterned lines, suggesting that cells may utilize different molecular pathways to sense curved topographies. Our study demonstrates that DLW can be employed to investigate the effects and mechanisms of topography on cell migration by fabricating a wide array of physiologically-relevant surfaces with curvatures that are challenging to fabricate using conventional manufacturing techniques.